2015
DOI: 10.1016/j.seizure.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in infants with West syndrome

Abstract: Our data suggest that the initial reduction in HRV in patients at the time of onset of WS is transient and related to the presence of hypsarrhythmia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…There are also treatment implications if HRV proves a reliable SUDEP biomarker, as certain therapies may have a beneficial effect on HRV. Children with infantile spasms have low HRV at the time of diagnosis, but this improves following treatment . As well, therapeutic application of vagal nerve stimulation (VNS) is associated with a reduction in T‐wave alternans, a measure of cardiac instability, making VNS an attractive candidate to reduce SUDEP risk; however, the effects of VNS on HRV have not yet been thoroughly studied, and a clear reduction in SUDEP incidence post‐VNS implantation has not been shown .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also treatment implications if HRV proves a reliable SUDEP biomarker, as certain therapies may have a beneficial effect on HRV. Children with infantile spasms have low HRV at the time of diagnosis, but this improves following treatment . As well, therapeutic application of vagal nerve stimulation (VNS) is associated with a reduction in T‐wave alternans, a measure of cardiac instability, making VNS an attractive candidate to reduce SUDEP risk; however, the effects of VNS on HRV have not yet been thoroughly studied, and a clear reduction in SUDEP incidence post‐VNS implantation has not been shown .…”
Section: Discussionmentioning
confidence: 99%
“…Children with infantile spasms have low HRV at the time of diagnosis, but this improves following treatment. 34,35 As well, therapeutic application of vagal nerve stimulation (VNS) is associated with a reduction in T-wave alternans, a measure of cardiac instability, making VNS an attractive candidate to reduce SUDEP risk; however, the effects of VNS on HRV have not yet been thoroughly studied, and a clear reduction in SUDEP incidence post-VNS implantation has not been shown. 36,37 In the future, clinicians may use sequential HRV measurements to assess whether a patient's SUDEP risk had changed on a given treatment.…”
Section: Future Directionsmentioning
confidence: 99%
“…A number of studies have investigated the effects of drug treatment on abnormal HRV in epilepsy. In some cases, such as the already‐discussed West syndrome, there are multiple studies with data that generally agree that there is HRV improvement following treatment initiation . In epilepsy with older childhood onset, autonomic balance also appears to partially normalize following treatment initiation as well …”
Section: Effects Of Treatment On Interictal Hrvmentioning
confidence: 98%
“…A fourth study examined HRV in sleep only found an increased LF component . Following treatment, there is a shift toward recovery of parasympathetic function …”
Section: Interictal Hrv Patterns In Different Epilepsy Typesmentioning
confidence: 99%
See 1 more Smart Citation